Menganalisis Neraca Pembayaran Sebagai Tolak Ukur Kemampuan Perekonomian Nasional dalam Menopang Transaksi - Transaksi Internasional - Darren Nataleano Metusalak Taulo; Iluh Nadila Rahma; Muhammad Yasin (Trending: Jurnal Manajemen dan Ekonomi, 2024)
The Indonesian economy is currently experiencing significant growth, which can be measured through its balance of payments. The balance of payments is a systematic record of international economic transactions between the residents of a country and those of other countries over a specific period of time. The development of the balance of payments is closely related to the growth of the real, fiscal, and monetary sectors. The balance of payments can be considered an indicator of a country's economic condition because it allows a country to measure the size of the flow of funds from abroad, both incoming and outgoing. The balance of payments also serves as an important tool, as it records all economic transactions involving the exchange of goods, services, and financial assets between the residents of a country and those of other countries.